A LIBER Passport? - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
The Bologna Process started on 19 June 1999, when 29 European Ministers responsible for Higher Education signed the Bologna declaration, in which they undertook to create a European Higher Education Area. The creation of the European Higher Education Area should be completed by 2010. The main objectives of the Bologna declaration are to increase the mobility and employability of European higher education graduates, thus ensuring competitiveness of European Higher Education on the world scale.